Challenges and Obstacles of Relocating the Nation's Capital - Iskandar, Ida Wahyuni; Hariati, Hariati (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2025)
President Joko Widodo accelerated the realisation of the capital city relocation and selected Penajam Paser Utara Regency and Kutai Kartanegara Regency in East Kalimantan as the location of the new capital city. On 15 February 2022, Law Number 3 of 2022 concerning the National Capital City (IKN Law) was passed and ratified. This paper uses a literature study method related to the IKN Nusantara. Through the literature study, information was obtained regarding the challenges and obstacles in relocating the capital. Relocating the capital requires a long process and is not easy. To realise the relocation of the IKN according to the targets that have been prepared, there are various challenges and obstacles including doubts about urgency, funding, environmental impacts, protection of the rights of local communities and indigenous peoples and the readiness of buffer zones